RGN-259 (thymosin β4) improves clinically important dry eye efficacies in comparison with prescription drugs in a dry eye model - Chae Eun Kim (Nature Portfolio, 2018)
Abstract This study evaluated the clinical activity of RGN-259 (thymosin β4) in comparison with cyclosporine A (CsA), diquafosol (DQS), and lifitegrast (LFA) in a murine model of dry eye. The model was NOD.B10-H2 b mice in a 30–40% humidified environment together with daily scopolamine hydrobromide injections for 10 days. After desiccation stress, all drugs were evaluated after 10 treatment days. RGN-259 increased tear production similar to that in the DQS- and LFA-treated mice while CsA was inactive. RGN-259 improved corneal smoothness and decreased fluorescein staining similar to that of LFA group while CsA and DQS were inactive. Corneal epithelial detachment was reduced by RGN-259, and DQS and LFA showed similar activity but the CsA was inactive. RGN-259 increased conjunctival goblet cells and mucin production comparable to that seen with CsA, while DQS and LFA were inactive. RGN-259 reduced the over-expression of inflammatory factors comparable to that with CsA and LFA, while DQS was inactive. RGN-259 increased mucin production comparable to that observed with CsA, while DQS and LFA were inactive. In conclusion, RGN-259 promoted recovery of mucins and goblet cells, improved corneal integrity, and reduced inflammation in a dry eye mouse model and was equal to or more effective than prescription treatments.